(untitled) (Bangladesh Journal of Public Administration, 2021)
Recent studies have suggested that e-commerce has opened up a window of opportunities for the national economy of Bangladesh with minimum capital investment by digitalizing the information. Thereby, it is important to unravel the ontology of e-commerce for deepening the understanding of this digital revolution. To serve this purpose the study has conducted a small-scale survey on 29 females and 21 males, ranging in age from 16 to more than 55, who are all online shoppers both in the form of buyers and sellers. To supplement data to the survey, 10 in-depth interviews, five sellers and five buyers, are also taken. The study finds that e-commerce is gradually getting popular among the growing young generation of 24-34 age groups. Almost 100% of female shoppers prefer clothing, personal products to buy while male shoppers prefer electronic goods more. E-commerce creates a substitute marketing channel by terminating the manipulative role of middleman. Moreover, it serves as an empowering tool for women entrepreneurs. On the contrary, a few shoppers perceive e-commerce negatively for de-socializing people and creating false needs among young generation. In addition, a lot of virtual risks are explored associated with online business. Despite having these risks, e-commerce has made people’s life easier and thereby people should welcome the positive sides to underwrite the gradual development of e-commerce for keeping pace with this fast-moving world.